Wolność wypowiedzi a ochrona dóbr osobistych osób pełniących funkcje publiczne - Sobczak, Jacek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Athorough analysis of mutual relations between freedom of speech and the protection of non-material values of individuals who perform public duties draws the author to the conclusion that a person performing public duties can easily become a subject of a more or less justified criticism of the public media; he or she can easily suffer damage to his or her honor or privacy. Each person holding a public post is practically helpless with regard to journalists who are not always willing to bear in mind the noble principles of conduct.